Josephson-based full digital bridge for high-accuracy impedance comparisons*Contribution of the National Institute of Standards and Technology, US Department of Commerce, not subject to copyright in the United States. (24th June 2016) - Overney, Frédéric; Flowers-Jacobs, Nathan E; Jeanneret, Blaise; Rüfenacht, Alain; Fox, Anna E; Underwood, Jason M; Koffman, Andrew D; Benz, Samuel P
Abstract: This paper describes a Josephson-based full digital impedance bridge capable of comparing any two impedances, regardless of type (R-C, R-L, or L-C), over a large frequency range (from 1 kHz to 20 kHz). At the heart of the bridge are two Josephson arbitrary waveform synthesizer systems that offer unprecedented flexibility in high-precision impedance calibration, that is, it can compare impedances with arbitrary ratios and phase angles. Thus this single bridge can fully cover the entire complex plane. In the near future, this type of instrument will considerably simplify the realization and maintenance of the various impedance scales in many National Metrology Institutes around the world.